2006
DOI: 10.1016/j.jcat.2006.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Continuous catalytic oxidation of solid alcohols in supercritical CO2: A parametric and spectroscopic study of the transformation of cinnamyl alcohol over Pd/Al2O3

Abstract: Cinnamyl alcohol was oxidized to cinnamaldehyde in a continuous fixed-bed reactor with molecular oxygen over an alumina-supported palladium catalyst in supercritical carbon dioxide modified with toluene. A strong dependence of the reaction performance on pressure and oxygen concentration in the feed was found. Optimization of the reaction conditions resulted in a higher catalytic activity than in liquid phase. At 120 bar, 80 °C, and double stoichiometric oxygen concentration, a turnover frequency of 400 h-1 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 57 publications
3
40
0
Order By: Relevance
“…The latter seems to be more reducing under the conditions applied and therefore does not show any deactivation due to surface oxidation of the Pd-particles. These XANES results are also supported by corresponding EXAFS data and fitting [15,16]. FIGURE 5.…”
Section: Benzyl and Cinnamyl Alcohol Oxidation In Supercritical Carbosupporting
confidence: 73%
“…The latter seems to be more reducing under the conditions applied and therefore does not show any deactivation due to surface oxidation of the Pd-particles. These XANES results are also supported by corresponding EXAFS data and fitting [15,16]. FIGURE 5.…”
Section: Benzyl and Cinnamyl Alcohol Oxidation In Supercritical Carbosupporting
confidence: 73%
“…But the reaction rates are typically lower, particularly since no base can be used [11,13]. An alternative approach is the employment of supercritical carbon dioxide § as an environmentally benign solvent, which was also recently used for selective alcohol oxidations [18][19][20][21][22][23][24]. In addition, since it allows performing the reaction in an inert and non-flammable medium at potentially high reaction rates [25][26][27], it provides several advantages from a process and catalytic point of view.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, no deactivation was observed on increasing the O 2 concentration under these scCO 2 conditions, suggesting palladium over-oxidation is not detrimental to selox. A parallel operando study of cinnamyl alcohol selox under scCO 2 confirmed that reactant-induced reduction was an important process, and that oxygen supply to the catalyst was mass-transport limited [150]. A related XAS investigation of untreated and Bi-promoted Pd/Al 2 O 3 for phenyl ethanol selox revealed that both the promoter and platinum were in a reduced state when 100 % selectivity to acetophenone was observed [151].…”
Section: X-ray Absorption Spectroscopymentioning
confidence: 87%